The Role of Product Quality and Service Quality to Increase Satisfaction and Build Consumer Loyalty: a Case Study of Sakato Restaurant in Malang - Aini, Nurul Qurrotul; Hapsari, Emilly Nur; Sary, Intan Umull Magfira; Asy’ari , Ahmad Taufiqurrahman; Sudarmiatin, Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the quality of service, product quality, consumer satisfaction, and consumer loyalty at Sakato Restaurant. This research uses a qualitative method with a case study approach and data collection techniques called observation and interviews. Findings from these observations and interviews place the quality of products and services at Sakato Restaurant in the favorable category, contributing to high levels of customer satisfaction and loyalty. This is evidenced by positive ratings across various platforms, as well as a strong inclination among consumers to make repeat purchases and recommend the restaurant to others. This study is expected to provide strategic recommendations to Sakato Restaurant to improve customer satisfaction and grow customer loyalty, while also adding insight into the importance of maintaining consistent product and service quality so that customers feel satisfied and become loyal.